(untitled) (Economic Journal of Nepal, 2019)
High absenteeism and dropout rates in school are considered one of the major stumbling blocks in achieving educational goals in developing countries. Absentees and dropouts impose a large resource cost on the educational system and the society. The study examines the economic cost of absentee and dropout students in public schools of Nepal. Using data from public schools in a rural municipality in Nepal, the study estimates the unit cost of absentee and dropout students by level. Cost of human resource, stationery, utility and fixed costs of building and furniture were the components for estimating unit costs. The findings reveal that the unit cost of students was equivalent to U.S. 295, 130 and 143 for primary, lower-secondary, and secondary levels respectively, and an average of U.S. 189 overall. The resource loss due to dropout was around 28, 12, and 11 percent of the total resource spent for primary, lower secondary and secondary levels respectively with an average of around 16 percent. The combined resource loss from dropouts and absentees were found to be 39, 23 and 20 percent for the different levels. On average, 26 percent of the public-school resource was lost due to dropouts and absentees. The main causes of dropout and absenteeism were the lack of interest, motivation of parents and the children to attend the school. The study suggests the need for more comprehensive and in depth study for effective policy formulation to address this problem.